Graphite-based negative electrode material and preparation method and application thereof
By covering the surface of the graphite core with hard carbon and soft carbon layers, controlling the layer spacing and particle size of the graphite core, the problems of insufficient rate performance and poor cycle stability in the fast charging process of existing graphite-based negative electrode materials are solved, and the mechanical strength of the material is improved and the cycle stability enhancement is enhanced.
Patent Information
- Application Number
- CN202510002489.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The existing graphite-based negative electrode materials have problems such as insufficient rate performance, large diffusion resistance, and poor cycle stability during fast charging. The use of strong acids during the preparation process leads to equipment corrosion and waste acid treatment problems.
By covering the surface of the graphite core with hard and soft carbon layers, the layer spacing and particle size of the graphite core are controlled, the mechanical strength and compaction density of the material are improved, and the risk of rupture during volume changes and cycling is reduced.
It improves the rate performance and fast charging performance of graphite-based anode materials, enhances cycle stability and mechanical strength, and reduces capacity attenuation and equipment corrosion risks.
Smart Images

Figure CN119812319A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of secondary batteries, and specifically relates to a graphite-based negative electrode material and a preparation method and application thereof. Background Art
[0002] With the development of society, the new energy industry has developed rapidly. New energy vehicles have driven the continuous increase in the output of lithium-ion batteries. Along with the market clients' demand for fast charging of lithium-ion batteries, the negative electrode with fast charging capability is currently a hot spot in research and development.
[0003] At present, graphite as a negative electrode active material still has the following problems during fast charging: (1) Graphite is an anisotropic material as a whole, which makes it impossible to embed lithium ions from all directions. It can only diffuse from the edge of the layer to the interior of the material. The long diffusion path limits its rate performance; (2) The layered structure of graphite can realize the embedding and detachment of lithium ions, but due to the small spacing between graphite layers (0.335nm), the diffusion resistance of lithium ions is large and the ideal rate performance cannot be achieved; (3) Due to the expansion of the spacing between graphite layers caused by the embedding of lithium ions, the volume expansion caused by long-term circulation will break the complete solid electrolyte interface membrane (SEI membrane), and the formation of a new SEI membrane will reduce the amount of active lithium, eventually leading to a cycle drop.
[0004] In order to solve the above problems, the prior art discloses a method for preparing micro-expanded graphite by chemical intercalation, which can expand the graphite interlayer spacing, increase the solid phase diffusion rate of lithium ions in graphite, and thus improve the rate performance of graphite negative electrode materials. However, in the process of preparing micro-expanded graphite, it is inevitable that large pores will be generated inside the graphite material, which will reduce the tapping performance of graphite; and the mechanical strength of large-porosity graphite is low, the ability to resist volume changes is weak, and the particle structure is prone to serious rupture during the cycle, so it is also necessary to solve the problem of low tap density by isostatic pressing. In addition, these methods in the prior art are mainly applicable to natural graphite, because natural graphite raw materials are flaky graphite, while artificial graphite is block graphite, and pickling and chemical intercalation agents cannot enter the block graphite; in addition, the reaction degree of the strong acid used as the intercalation agent is not easy to control, and the use of strong acid intercalation agents is a severe challenge for processing equipment corrosion and waste acid treatment. Summary of the invention
[0005] Therefore, the technical problem to be solved by the present application is to overcome the above-mentioned defects of the micro-expanded graphite negative electrode material and its preparation process in the prior art, thereby providing a graphite-based negative electrode material and its preparation method and application.
[0006] To this end, this application provides the following technical solutions:
[0007] According to one aspect of the present application, a graphite-based negative electrode material is provided, comprising:
[0008] A graphite core, wherein the interlayer spacing of the graphite core is 0.337 to 0.342 nm; and the average particle size of the graphite core is 6 to 9 μm;
[0009] A first shell layer, covering at least a portion of the surface of the graphite core, wherein the first shell layer is a hard carbon coating layer;
[0010] A second shell layer, covering at least a portion of the surface of the first shell layer, wherein the second shell layer is a soft carbon coating layer;
[0011] Wherein, the ratio of the average particle size of the graphite-based negative electrode material to the average particle size of the graphite core is 1.5 to 1.8.
[0012] In the present application, the first shell and the second shell can be distinguished by conventional detection means in the field. As an example, Raman and XRD can be used for distinction, and there are differences in the peak positions and peak intensities of the two. Among them, the peak position of the first shell in the Raman spectrum is 1580cm -1 (G peak) and 1360cm -1 Near (D peak), the intensity ratio of D peak to G peak (ID / IG) is 0.9-1.2; the interlayer spacing of (002) crystal plane calculated by Bragg equation in XRD test is 0.35-0.37nm. The peak position of the second shell in Raman spectrum is 1590cm -1 (G peak) and 1350cm -1 (D peak), the intensity ratio of D peak to G peak (ID / IG) is 0.5-0.9; the interlayer spacing of the (002) crystal plane calculated by the Bragg equation in the XRD test is 0.342-0.350nm.
[0013] In this application, known methods and equipment in the field can be used to test the graphite interlayer spacing. As an example, the specific test method includes the following steps: take 1.2g of material and 0.8g of silicon powder mixed sample, grind evenly, take an appropriate amount and place it on the sample holder to flatten, turn on the X-RAY device for testing, and use highScore software to fit and calculate the interlayer spacing d 002 .
[0014] In the present application, the average particle size of the graphite raw material core and the final product is tested by methods and equipment known in the art. As an example, the specific testing method includes the following steps: adding about 0.02g of powder sample to a 50ml clean beaker, adding about 20ml of deionized water, and then dropping 0.2mL of 1wt% surfactant NP-40 to completely disperse the powder in water, ultrasonically cleaning in a 120W ultrasonic cleaning machine for 1 minute, and testing the particle size distribution using a MasterSizer 3000, where the volume particle size distribution D50 is the average particle size.
[0015] In some optional embodiments, based on the total mass of the graphite-based negative electrode material, the mass of the first shell layer accounts for 1% to 3%.
[0016] In some optional embodiments, based on the total mass of the graphite-based negative electrode material, the mass of the second shell layer accounts for 1% to 3%.
[0017] In the present application, methods and equipment known in the art can be used to test the mass proportion of the first shell layer. As an example, the specific testing method includes the following steps: gently place the material to be weighed on the platform of the electronic scale, and ensure that the center of gravity of the object is located in the center of the scale. Wait for the value on the display of the electronic scale to stabilize and then record the result. Add or reduce the material according to the difference between the displayed result and the required mass.
[0018] In the present application, methods and equipment known in the art can be used to test the mass proportion of the second shell. As an example, the specific testing method includes the following steps: gently place the material to be weighed on the platform of the electronic scale, ensuring that the center of gravity of the item is located in the center of the scale. Wait for the value on the display of the electronic scale to stabilize and then record the result. Add or reduce the material according to the difference between the displayed result and the required mass.
[0019] In some optional embodiments, the graphite core includes at least one of artificial graphites.
[0020] In this application, the compaction density of the graphite-based negative electrode material is tested using methods and equipment known in the art. As an example, the specific test method includes the following steps: weighing 1.0000g±0.0100g of sample, adding the weighed sample to the mold of the press, inputting the sample name and sample mass in the software interface, and measuring the powder compaction density using a powder compactor UTM7305. The test pressure in this application is 5T.
[0021] According to another aspect of the present application, a method for preparing a graphite-based negative electrode material is provided, comprising the following steps:
[0022] S1, crushing the graphite raw material, and controlling the average particle size of the crushed material to be A;
[0023] S2, mixing the crushed material with a high aromatic oil, and pyrolyzing the mixture to obtain an intermediate having a first shell layer;
[0024] S3, subjecting the intermediate to low-temperature graphitization treatment at a temperature of 1800 to 2400° C. to obtain a graphitized product;
[0025] S4, heat-treating the graphitized product under a protective atmosphere, wherein the heat-treating pressure is 0.2-2 MPa, the temperature is 300-600° C., and the time is 3-12 h;
[0026] S5, mixing the product after heat treatment with a soft carbon raw material, performing carbonization, demagnetization, and screening, and controlling the average particle size B of the graphite-based negative electrode material to satisfy the following relationship: 1.5≤B / A≤1.8.
[0027] In some optional embodiments, in step S1, the average particle size A of the material after pulverization is controlled to be 6 to 9 μm;
[0028] and / or, in step S2, the mass ratio of the crushed material to the high aromatic oil is 100:5-20;
[0029] And / or, in step S5, the mass ratio of the product after the heat treatment to the soft carbon raw material is 100:5-20.
[0030] In some optional embodiments, the method for preparing the graphite-based negative electrode material satisfies at least one of the following (1) to (7):
[0031] (1) In step S2, the pyrolysis temperature is 300 to 800° C. and the time is 0.5 to 2 h;
[0032] (2) In step S3, the low-temperature graphitization treatment time is 8 to 40 hours;
[0033] (3) In step S5, the heating rate of the carbonization treatment is 1 to 5°C / min;
[0034] (4) The temperature of the carbonization treatment is 800 to 1200° C.; the time of the carbonization treatment is 6 to 12 hours;
[0035] (5) the high aromatic oil comprises at least one of creosote oil, naphthalene oil or anthracene oil;
[0036] (6) The graphite raw material includes at least one of needle coke, petroleum coke, and asphalt coke;
[0037] (7) The soft carbon raw material includes at least one of asphalt, rubber plasticizer, carbon fiber, and carbon microspheres.
[0038] In the present application, the pulverizing equipment in step S1 is conventional in the field, including but not limited to one or more of roller mill and mechanical mill;
[0039] In the present application, the mixing equipment used in the mixing step is conventional in the art, including but not limited to one or more of a fusion machine and a mixer.
[0040] According to another aspect of the present application, a negative electrode plate is provided, comprising the above-mentioned graphite-based negative electrode material or the graphite-based negative electrode material prepared by the above-mentioned preparation method.
[0041] According to another aspect of the present application, a secondary battery is provided, comprising the above-mentioned negative electrode plate.
[0042] According to another aspect of the present application, there is provided an electrical device comprising the above-mentioned secondary battery.
[0043] In the present application, the high aromatic oil refers to a component with a relatively high aromatic content, for example, an aromatic content of 60 to 85% by mass.
[0044] In the present application, the composition and preparation method of the negative electrode sheet are conventional in the field. Typically, but not limitedly, the negative electrode composite material, conductive carbon black, binder (styrene-butadiene rubber SBR) and thickener (sodium carboxymethyl cellulose CMC) are mixed in a weight ratio of about 95-97:0.5-1.5:1-2:1-2, and an appropriate amount of deionized water is added to prepare a slurry with a solid content of 50-70wt% and knead to form a dough-like material; then an appropriate amount of deionized water is added to adjust the viscosity of the slurry to 3000-8000Pa·S to prepare a negative electrode slurry. The prepared negative electrode slurry is coated on the negative electrode current collector copper foil (thickness 8μm), dried at room temperature, and then transferred to a 100-140℃ oven for drying for 0.5-2h, and then cold pressed and cut to obtain a negative electrode sheet.
[0045] In the present application, the secondary battery also includes a positive electrode sheet, an electrolyte and a separator, etc. The specific composition and preparation method are conventional in the field. Typically, the positive electrode material LiFePO4, the binder PVDF, and the conductive agent acetylene black are mixed according to a mass ratio of 93 to 96:2 to 4:2 to 4, and N-methylpyrrolidone (NMP) solvent is added until the system becomes uniform and transparent. After stirring with a vacuum mixer, a positive electrode slurry is obtained, which is then evenly coated on a current collector aluminum foil (thickness of 12 μm), dried at room temperature, and then transferred to a 100 to 140 ° C oven for drying for 0.5 to 2 hours, and then cold pressed (compacted density of 2.3 to 2.6 g / cm 3), cut to obtain the positive electrode sheet. The positive electrode sheet, the negative electrode sheet and the polypropylene porous polymer film are wound, wrapped with aluminum plastic film, baked to remove water, and then injected with electrolyte and sealed. After standing, hot and cold pressing, formation, clamping, capacity division and other processes, a soft-pack lithium-ion battery is prepared.
[0046] The electrolyte used in the secondary battery of the present application may include any technology disclosed in the prior art.
[0047] In the present application, the secondary battery can be used as a power source for the electrical equipment or as an energy storage unit for the electrical equipment. The electrical equipment can be, but is not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0048] The technical solution of this application has the following advantages:
[0049] The graphite-based negative electrode material provided in the present application includes: a graphite core, the interlayer spacing of the graphite core is 0.337 to 0.342 nm; a first shell layer, coated on at least a portion of the surface of the graphite core, the first shell layer is a hard carbon coating layer; a second shell layer, coated on at least a portion of the surface of the first shell layer, the second shell layer is a soft carbon coating layer, wherein the ratio of the average particle size of the graphite-based negative electrode material to the average particle size of the graphite core is 1.5 to 1.8. This application controls the interlayer spacing of the graphite core to make the resistance of lithium / sodium insertion smaller, which helps the rapid charging and discharging process of the graphite negative electrode material and is beneficial to the cycle stability; by coating the surface of the graphite core with a hard carbon layer, the mechanical strength of the graphite can be improved, the volume change can be reduced, and the particle structure rupture and the generation of a new SEI film caused by volume expansion during the cycle can be avoided; the outermost layer is coated with a soft carbon layer for granulation, which improves the compaction density of the negative electrode material, and at the same time forms secondary particles with higher isotropy, forming a stable amorphous carbon structure, avoiding direct contact between the graphite core and the electrolyte, and protecting the internal graphite. This application improves the rate performance and fast charging performance of the material while improving the compaction density and mechanical strength of the material and reducing the volume expansion rate during the cycle by controlling the interlayer spacing of the graphite core, limiting the specific composition of the first shell and the second shell, and limiting the ratio of the particle size of the graphite core and the graphite-based negative electrode material.
[0050] The preparation method of the graphite-based negative electrode material provided in the present application, S1, crushing the graphite raw material, and controlling the average particle size of the crushed material to be A; S2, mixing the crushed material with high aromatic oil, pyrolyzing, and obtaining an intermediate with a first shell layer; S3, low-temperature graphitization treatment of the intermediate, the treatment temperature is 1800-2400°C, to obtain a graphitized product; S4, heat-treating the graphitized product under a protective atmosphere, the heat treatment pressure is 0.2-2Mpa, the temperature is 300-600°C, and the time is 3-12h; S5, mixing the product after the heat treatment with asphalt, carbonizing, demagnetizing, and screening, and controlling the average particle size B of the graphite-based negative electrode material to satisfy the following relationship: 1.5≤B / A≤1.8. This application is designed for the graphite core interlayer spacing and material size to improve the kinetic performance and cycle life of graphite-based negative electrode materials. At the same time, considering the material manufacturing possibility and material processing performance, no strong acid is used, avoiding the corrosion of strong acid materials to processing equipment and the problem of handling and discharging waste acid. The large interlayer spacing of the graphite core reduces the volume expansion caused by the lithium insertion process to a certain extent, reduces the consumption of cathode lithium, improves the cycle performance, and effectively inhibits capacity decay. Moreover, this process is basically the same as the conventional graphite synthesis process, and there is no need for large-scale transformation of the production line. The manufacturing cost is low and it is easy to promote and apply. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0052] Figure 1 It is a schematic diagram of the structure of the graphite-based negative electrode material provided in this application;
[0053] Reference numerals:
[0054] 1. Graphite core; 2. First shell; 3. Second shell. DETAILED DESCRIPTION
[0055] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.
[0056] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0057] Example 1
[0058] This embodiment provides a graphite-based negative electrode material, and its structural schematic diagram is as follows: Figure 1 As shown, it includes a graphite core 1, a first shell layer 2 coated on at least a portion of the surface of the graphite core 1, and a second shell layer 3 coated on at least a portion of the surface of the first shell layer 2. The specific preparation method includes the following steps:
[0059] (1) grinding the graphite raw material needle coke (needle coke GHBA-1 produced by Qingdao Phillips 66 Energy Co., Ltd.) to obtain a particle size A of 7.8 μm;
[0060] (2) The crushed powder particles are mixed evenly with naphthalene oil (an organic substance distilled from coal tar at about 220° C., the same below) in a mass ratio of 100:15;
[0061] (3) The reaction furnace is heated and burned at a combustion temperature of 600°C. The mixed material is sprayed into the burning flame and reacts for 1 hour. It is rapidly pyrolyzed at high temperature to form a hard carbon coating layer (i.e., the first shell layer) on the surface;
[0062] (4) subjecting the pyrolyzed particles to low-temperature graphitization at a graphitization temperature of 2000°C for a treatment time of 20 h;
[0063] (5) placing the dry powder obtained after graphitization in step (4) into a sealed reactor, adding nitrogen protection, setting the furnace pressure to 0.4 MPa, heating at 400° C. for 6 h, and then naturally cooling the reactor to room temperature to obtain a large interlayer spacing graphite core;
[0064] (6) putting the product obtained in step (5) and asphalt (softening point 200° C., the same below) into a mechanical fusion device at a mass ratio of 100:10 for mixing;
[0065] (7) The mixture mixed in step (6) is carbonized at a temperature of 1000° C. for 8 h at a heating rate of 10° C. / min, and demagnetized and sieved to control the average particle size B of the graphite-based negative electrode material (the average particle size of the final product) to the average particle size A of the negative electrode material after pulverization to be: B / A=1.72.
[0066] Example 2
[0067] This embodiment provides a graphite-based negative electrode material. Compared with Example 1, the difference is that the average particle size of the graphite raw material and the final product is controlled differently. The specific differences in parameters and the differences in the final graphite-based negative electrode material final product are detailed in Table 1.
[0068] Example 3
[0069] This embodiment provides a graphite-based negative electrode material. Compared with Example 1, the difference lies in the different graphitization temperature. The specific differences in parameters and the differences in the final graphite-based negative electrode material final product are detailed in Table 1.
[0070] Example 4
[0071] This embodiment provides a graphite-based negative electrode material. Compared with Example 1, the difference is that anthracene oil of equal mass is used instead of naphthalene oil, the particle size control of the graphite raw material is different, and the specific differences in parameters and the differences in the final graphite-based negative electrode material final product are detailed in Table 1.
[0072] Example 5
[0073] This embodiment provides a graphite-based negative electrode material. Compared with Example 4, the difference is that the particle size control of the graphite raw material is different. The specific differences in parameters and the differences in the final graphite-based negative electrode material final product are detailed in Table 1.
[0074] Example 6
[0075] This embodiment provides a graphite-based negative electrode material. Compared with Example 1, the difference is that the graphitization temperature is different, an equal mass of creosote oil (boiling point is 220° C., the same below) is used instead of naphthalene oil, and the particle size control of the graphite raw material is different. The specific differences in parameters and the differences in the final graphite-based negative electrode material final product are detailed in Table 1.
[0076] Example 7
[0077] This embodiment provides a graphite-based negative electrode material. Compared with Example 1, the difference lies in the different control of graphitization temperature and the pulverization particle size of the graphite raw material. The specific differences in parameters and the differences in the final graphite-based negative electrode material final product are detailed in Table 1.
[0078] Example 8
[0079] This embodiment provides a graphite-based negative electrode material. Compared with Example 1, the difference lies in the different control of graphitization temperature and the pulverization particle size of the graphite raw material. The specific differences in parameters and the differences in the final graphite-based negative electrode material final product are detailed in Table 1.
[0080] Example 9
[0081] This embodiment provides a graphite-based negative electrode material. Compared with Example 6, the difference is that the particle size control of the graphite raw material is different. The specific differences in parameters and the differences in the final graphite-based negative electrode material final product are detailed in Table 1.
[0082] Example 10
[0083] This embodiment provides a graphite-based negative electrode material. Compared with Example 7, the difference lies in the different control of the pulverized particle size of the graphite raw material. The specific differences in parameters and the differences in the final graphite-based negative electrode material final product are detailed in Table 1.
[0084] Embodiment 11
[0085] This embodiment provides a graphite-based negative electrode material. Compared with Example 1, the difference is that an equal mass of petroleum coke (upper petroleum coke of Shandong Yida New Materials Co., Ltd.) is used to replace the needle coke in Example 1. The specific differences in parameters and the differences in the final graphite-based negative electrode material final product are detailed in Table 1.
[0086] Example 12
[0087] This embodiment provides a graphite-based negative electrode material. Compared with Example 1, the difference is that in step S6, an equal mass of rubber plasticizer (Liaoning Xinde New Materials, model XD-Y) is used instead of asphalt. The specific differences in parameters and the differences in the final graphite-based negative electrode material final product are detailed in Table 1.
[0088] Comparative Example 1
[0089] This comparative example provides a graphite-based negative electrode material. Compared with Example 1, the difference is that the interlayer spacing and particle size of the graphite core are controlled differently by regulating the graphitization temperature. The specific differences in parameters and the differences in the final graphite-based negative electrode material final product are detailed in Table 1.
[0090] Comparative Example 2
[0091] This comparative example provides a graphite-based negative electrode material. Compared with Example 1, the difference is that the interlayer spacing and particle size of the graphite core are controlled differently by regulating the graphitization temperature. The specific differences in parameters and the differences in the final graphite-based negative electrode material final product are detailed in Table 1.
[0092] Comparative Example 3
[0093] This comparative example provides a graphite-based negative electrode material. Compared with Example 1, the difference lies in the different particle size control. The specific differences in parameters and the differences in the final graphite-based negative electrode material final products are shown in Table 1.
[0094] Comparative Example 4
[0095] This comparative example provides a graphite-based negative electrode material. Compared with Example 4, the difference lies in the different particle size control. The specific differences in parameters and the differences in the final graphite-based negative electrode material final product are shown in Table 1.
[0096] Comparative Example 5
[0097] This comparative example provides a graphite-based negative electrode material. Compared with Example 1, the difference is that an equal mass of asphalt is used instead of naphthalene oil in step (2). The specific differences in parameters and the differences in the final graphite-based negative electrode material product obtained are detailed in Table 1.
[0098] Comparative Example 6
[0099] This comparative example provides a graphite-based negative electrode material. Compared with Example 1, the difference is that step (2) is not included, and the crushed graphite raw material is directly subjected to subsequent steps such as step (3). The specific differences in parameters and the differences in the final graphite-based negative electrode material final product are detailed in Table 1.
[0100] Comparative Example 7
[0101] This comparative example provides a graphite-based negative electrode material. Compared with Example 1, the difference is that step (6) is not included, and the product obtained in step (5) is directly subjected to subsequent steps such as carbonization in step (7). The specific differences in parameters and the differences in the final graphite-based negative electrode material product are detailed in Table 1.
[0102] Table 1
[0103]
[0104]
[0105] Test Case
[0106] Battery cell testing
[0107] Preparation of negative electrode sheet:
[0108] The graphite-based negative electrode material, conductive carbon black, binder (styrene-butadiene rubber SBR) and thickener (sodium carboxymethyl cellulose CMC) provided in each embodiment and comparative example are mixed in a weight ratio of about 96:1:1.6:1.4 to obtain 100 kg of the mixture, and an appropriate amount of deionized water is added to prepare a slurry with a solid content of 60wt%, and kneaded to form a dough-like material; then an appropriate amount of deionized water is added to adjust the viscosity of the slurry to about 5000Pa·S to prepare a negative electrode slurry. The prepared negative electrode slurry is coated on the negative electrode current collector copper foil (thickness of 8μm), and the negative electrode surface density is 120-160g / m 2 (The surface density in this test example is 140g / m 2), dried at room temperature and then transferred to a 120°C oven for drying for 1 h, and then cold pressed and cut to obtain the negative electrode sheet.
[0109] Preparation of positive electrode sheet: positive electrode material LiFePO4, binder PVDF, and conductive agent acetylene black were mixed in a mass ratio of 94:3:3, N-methylpyrrolidone (NMP) solvent was added until the system became uniform and transparent, and the positive electrode slurry was prepared by stirring with a vacuum mixer, and then evenly coated on the current collector aluminum foil (thickness of 12 μm), dried at room temperature, transferred to a 120 ° C oven for 1 h, and then cold pressed (compacted density of 2.5 g / cm 3 ) and cut to obtain the positive electrode sheet.
[0110] Battery assembly: The positive electrode sheet, negative electrode sheet and polypropylene porous polymer film (AS9-1 of Enjie Co., Ltd.) are wound, wrapped with aluminum-plastic film, baked to remove water, and then injected with electrolyte (LD-124B of Dongguan Shanshan Battery Materials Co., Ltd.) and sealed. After standing, hot and cold pressing, formation, clamping, capacity division and other processes, a soft-pack lithium-ion battery (capacity of 3Ah, length, width and height of 120mm×70mm×30mm) is prepared.
[0111] 1. 3C charging rate test:
[0112] At 25°C, discharge at 0.33C to 2.0V, let stand for 5 minutes, charge at 3C to 3.65V, charge at constant voltage to 0.05C and let stand for 5 minutes, read the constant current charging capacity and total charging capacity, the ratio of the two is the 3C rate performance.
[0113] 2. High temperature cycle performance test:
[0114] The test temperature is 45℃, and the battery is charged to 3.65V at 1C constant current, charged to 0.05C at constant voltage, and discharged to 2.0V at 1C after standing for 5 minutes. The capacity obtained in this step is taken as the initial capacity, and a 1C charge / 1C discharge cycle test is performed. The capacity retention rate after 500 cycles at 45℃ is recorded to compare the high temperature cycle performance of the battery.
[0115] 3. Electrode assembly full charge expansion rate test:
[0116] The thickness of the fresh electrode assembly is tested with a spiral micrometer. When the cycle reaches 500, the electrode assembly is in a fully charged state. The thickness of the electrode assembly at this time is tested with a spiral micrometer again. By comparing it with the initial thickness of the fresh electrode assembly, the expansion rate of the fully charged electrode assembly can be obtained.
[0117] The specific test results are shown in the table below:
[0118] Table 2
[0119]
[0120]
[0121] It can be seen from the data in the above table that, according to the comparison between Examples 1 to 3 and Comparative Examples 1 to 2, by adjusting the interlayer spacing of the graphite core within the specified range of this application, the 3C rate performance and 45°C cycle retention rate of the negative electrode material are significantly improved, and the battery cell expansion rate is reduced. According to the comparison between Examples 1 to 3 and Comparative Examples 3 to 4, it can be seen that through special size design, the 3C rate performance and 45°C cycle retention rate of the obtained graphite-based negative electrode material are significantly improved. Comparative Example 5 uses different types of coating layers of equal mass. Compared with Examples 1 to 3, the interlayer spacing of graphite cannot be increased in the subsequent heat treatment step, and the 3C rate performance and 45°C cycle retention rate of the obtained graphite-based negative electrode material are reduced. Because Comparative Example 6 does not have the first shell layer, it is impossible to adjust the graphite core interlayer spacing within the specified range. Compared with Examples 1 to 2, the 3C rate performance, 45°C cycle retention rate and cycle expansion performance are all deteriorated. Since Comparative Example 7 does not have a second shell layer, the graphite size cannot be controlled to be within a limited range. Compared with Examples 1 to 2, the 3C rate performance, 45°C cycle retention rate, and cycle expansion performance deteriorate more significantly.
[0122] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A graphite-based negative electrode material, characterized in that: include: A graphite core, wherein the interlayer spacing of the graphite core is 0.337 to 0.342 nm; and the average particle size of the graphite core is 6 to 9 μm; A first shell layer, covering at least a portion of the surface of the graphite core, wherein the first shell layer is a hard carbon coating layer; A second shell layer, covering at least a portion of the surface of the first shell layer, wherein the second shell layer is a soft carbon coating layer; Wherein, the ratio of the average particle size of the graphite-based negative electrode material to the average particle size of the graphite core is 1.5 to 1.
8.
2. The graphite-based negative electrode material according to claim 1, characterized in that: Based on the total mass of the graphite-based negative electrode material, the mass of the first shell layer accounts for 1% to 3%.
3. The graphite-based negative electrode material according to claim 1, characterized in that: Based on the total mass of the graphite-based negative electrode material, the mass of the second shell layer accounts for 1% to 3%.
4. The graphite-based negative electrode material according to any one of claims 1 to 3, characterized in that: The graphite core includes at least one of artificial graphites.
5. A method for preparing a graphite-based negative electrode material, characterized in that: The steps include: S1, crushing the graphite raw material, and controlling the average particle size of the crushed material to be A; S2, mixing the crushed material with a high aromatic oil, and pyrolyzing the mixture to obtain an intermediate having a first shell layer; S3, subjecting the intermediate to low-temperature graphitization treatment at a temperature of 1800 to 2400° C. to obtain a graphitized product; S4, heat-treating the graphitized product under a protective atmosphere, wherein the heat-treating pressure is 0.2-2 MPa, the temperature is 300-600° C., and the time is 3-12 h; S5, mixing the product after heat treatment with a soft carbon raw material, performing carbonization, demagnetization, and screening, and controlling the average particle size B of the graphite-based negative electrode material to satisfy the following relationship: 1.5≤B / A≤1.
8.
6. The method for preparing a graphite-based negative electrode material according to claim 5, characterized in that: In step S1, the average particle size A of the crushed material is controlled to be 6 to 9 μm; and / or, in step S2, the mass ratio of the crushed material to the high aromatic oil is 100:5-20; And / or, in step S5, the mass ratio of the product after the heat treatment to asphalt is 100:5-20.
7. The method for preparing a graphite-based negative electrode material according to claim 5 or 6, characterized in that: Satisfy at least one of the following (1) to (7): (1) In step S2, the pyrolysis temperature is 300 to 800° C. and the time is 0.5 to 2 h; (2) In step S3, the low-temperature graphitization treatment time is 8 to 40 hours; (3) In step S5, the heating rate of the carbonization treatment is 1 to 5°C / min; (4) The temperature of the carbonization treatment is 800 to 1200° C.; the time of the carbonization treatment is 6 to 12 hours; (5) the high aromatic oil comprises at least one of creosote oil, naphthalene oil or anthracene oil; (6) The graphite raw material includes at least one of needle coke, petroleum coke, and asphalt coke; (7) The soft carbon raw material includes at least one of asphalt, rubber plasticizer, carbon fiber, and carbon microspheres.
8. A negative electrode plate, characterized in that: It comprises the graphite-based negative electrode material according to any one of claims 1 to 4 or the graphite-based negative electrode material prepared by the preparation method according to any one of claims 5 to 7.
9. A secondary battery, characterized in that: Including the negative electrode sheet as described in claim 8.
10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.
Citation Information
Patent Citations
Hard carbon and soft carbon co-modified artificial graphite negative electrode material and preparation method thereof
CN114852991A
High-compaction high-rate artificial graphite negative electrode material and preparation method thereof
CN115425206A
Graphite negative electrode material and lithium ion battery using same
CN116885155A
Preparation method of lithium ion battery material
CN117623299A
Graphite negative electrode material and preparation method thereof, negative electrode plate and lithium ion battery
CN117747783A